The Gospels according to St. Matthew, St. Mark, St. Luke, [and St. John] [electronic resource] (London : Printed by W. M'Dowall ., 1813)
Translated by the Rev. C.F. Burghardt--Cf. Bibliographies of the languages of the North American Indians (v. 1) / J.C. Pilling. The work does not contain the Gospel of John. "Printed for the use of the Mission, by the British and Foreign Bible Society." Electronic reproduction. Mode of access: Internet. 44